A Typology of Multiple School Leadership - Yin-Cheong Cheng (MDPI AG, 2024)
In facing the challenges of huge transformations in different areas of society, many educators, policy makers, social leaders, researchers and other stakeholders may doubt how schools and their leadership and management remain relevant to and effective for the future of education. Given that multiple school functions are needed to serve society at different levels, the required roles in school leadership are inevitably multiple, diverse and demanding. In past decades, many studies have been conducted with a focus on some aspects of leadership functions and processes. Unfortunately, there is a lack of a typology of school leadership to map out comprehensive leadership profiles and understand their multiple characteristics for leading school development and effectiveness in a fast-changing environment. Based on the framework of multiple school effectiveness, this paper aims to propose a typology of multiple school leadership that can provide a new, comprehensive way to re-conceptualize the multiple nature and characteristics of school leadership in a complicated context. Depending on the rationalities, concerns, actions, outcomes and contexts of leadership in practice, the typology of multiple school leadership may include six models: technological leadership, economic leadership, social leadership, political leadership, cultural leadership, and learning leadership. Within this typology, new possibilities and approaches to school leadership can be drawn for research, practice and development towards the future.